Value of intra- and post-operative cone beam computed tomography (CBCT) for positioning control of a sphenopalatine ganglion neurostimulator in patients with chronic cluster headache. Issue 3 (April 2015) - Assaf, Alexandre T.; Klatt, Jan C.; Blessmann, Marco; Kohlmeier, Carsten; Friedrich, Reinhard E.; Pohlenz, Philipp; May, Arne; Heiland, Max; Jürgens, Tim P.
Abstract Introduction The objective of this study was to determine whether postoperative control of the neurostimulator placement within the pterygopalatine fossa (PPF) by means of 3-dimensional (3D) cone beam computed tomography (CBCT) was of therapeutic relevance compared to intraoperative CBCT imaging alone. Material and methods Immediately after implantation of the sphenopalatine ganglion (SPG) neurostimulator, intraoperative CBCT datasets were generated in order to visualize the position of the probe within the PPF. Postoperatively, all patients received a CBCT for comparison with intraoperatively acquired radiographs. Results Twenty-four patients with cluster headache (CH) received an SPG neurostimulator. In 4 patients, postoperative CBCT images detected misplacement not found in intraoperative CBCT. In 3 cases, electrode tips were misplaced into the maxillary sinus and in 1 case into the apex of the PPF superior to the suspected location of the SPG. Immediate revision with successful repositioning within 3 days was done in 2 patients and a deferred reimplantation in 1 patient within 6 months. One patient declined revision. Conclusion We were able to demonstrate the clinical value of postoperative dental CBCT imaging with a wide region of interest (ROI) due to a superior image quality compared with that achieved with intraoperative medical CBCT. Although intraoperative 3D CBCT imaging of electrode placement is helpful in the acute surgical setting, resolution is, at present, too low to safely exclude misplacement, especially in the maxillary sinus. High-resolution postoperative dental CBCT allows rapid detection and revision of electrode misplacement, thereby avoiding readmission and recurrent tissue trauma.